Structural Stability and Performance of Noble Metal-Free SnO(2)-Based Gas Sensors - Tricoli, Antonio (Biosensors (Basel), 2012)
The structural stability of pure SnO(2) nanoparticles and highly sensitive SnO(2)-SiO(2) nanocomposites (0–15 SiO(2) wt%) has been investigated for conditions relevant to their utilization as chemoresistive gas sensors. Thermal stabilization by SiO(2) co-synthesis has been investigated at up to 600 °C determining regimes of crystal size stability as a function of SiO(2)-content. For operation up to 400 °C, thermally stable crystal sizes of ca. 24 and 11 nm were identified for SnO(2) nanoparticles and 1.4 wt% SnO(2)-SiO(2) nanocomposites, respectively. The effect of crystal growth during operation (T(O) = 320 °C) on the sensor response to ethanol has been reported, revealing possible long-term destabilization mechanisms. In particular, crystal growth and sintering-neck formation were discussed with respect to their potential to change the sensor response and calibration. Furthermore, the effect of SiO(2) cosynthesis on the cross-sensitivity to humidity of these noble metal-free SnO(2)-based gas sensors was assessed.